2002
DOI: 10.1097/00130478-200201000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pepsin and glucose in tracheal secretions as indicators of aspiration in mechanically ventilated children

Abstract: Pepsin is detectable in tracheal secretions of mechanically ventilated children at risk for aspiration. Elevated glucose concentrations in tracheal secretions can occur by mechanisms other than aspiration of glucose-rich formula. Pepsin may be a more specific marker for aspiration than glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
3
26
1
Order By: Relevance
“…In keeping with our findings, pepsin detection in throat sputum has been suggested to be a sensitive and non-invasive diagnostic method for laryngopharyngeal reflux [20]. Our study supports previous studies on the identification of pepsin in airway secretions for the diagnosis of laryngopharyngeal reflux [26,27,28,29]. Pepsin was detected mainly in the samples collected at the time of symptoms (n = 18).…”
Section: Discussionsupporting
confidence: 91%
“…In keeping with our findings, pepsin detection in throat sputum has been suggested to be a sensitive and non-invasive diagnostic method for laryngopharyngeal reflux [20]. Our study supports previous studies on the identification of pepsin in airway secretions for the diagnosis of laryngopharyngeal reflux [26,27,28,29]. Pepsin was detected mainly in the samples collected at the time of symptoms (n = 18).…”
Section: Discussionsupporting
confidence: 91%
“…Additional modifications of our laboratory procedures to detect lower levels of amylase are warranted; however, the values we obtained were similar to those reported for patients receiving mechanical ventilation who had risk factors for aspiration and infections. 5,7,8 Our findings are consistent with those of other reports 5,6,[8][9][10][11][12]14,[26][27][28][29][30][31][32][33][34][35][36] of pepsin and amylase as biomarkers of microaspiration. Dewavrin and colleagues 36 argue that the use of amylase is only moderately accurate in diagnosing microaspiration.…”
Section: Discussionsupporting
confidence: 92%
“…However, as shown in their study, it was possible to detect intracellular milk proteins only during the first 4 d following aspiration. Recently, Metheny and colleagues demonstrated that aspiration of gastric content could be detected by a specific pepsin immunoassay in tube-fed adults (24) and children (25) receiving mechanical ventilation and in an experimental model in rabbits (26). Although the technique is very sensitive for the diagnosis of aspiration secondary to gastroesophageal reflux, it does not detect aspiration from above due to disturbances such as swallowing mechanism dysfunction.…”
Section: Discussionmentioning
confidence: 99%